Product focus: a study on the product process at Ayuma Enterprise / Maliha Luie, Ramlah Salleh and Zaimah Tayon - Luie, Maliha; Salleh, Ramlah; Tayon, Zaimah (2014)
This study is to investigate the process in the product focus at Ayuma Enterprise (AE) and to examine why it cannot meet the increased demand for its laksa paste. Data collected from the semi-structured interviews with key person and employees of AE were analysed using three selected tools; the SWOT Analysis, the Fishbone Diagram and Time-function Mapping. AE's product is not variety in nature and its production is based on forecasted demand. Hence, meeting demand is of utmost important to its operations. Based on the findings, problems associated with meeting demand have been identified and some recommendations on how to improve its production capacity are discussed in this paper. The SWOT Analysis provides the internal and external assessments of AE. Meanwhile, the Fishbone Diagram analysis shows the root cause of the company's problem in meeting demand lies in its production process. The time-function mapping clearly shows that the time for each cycle of production can be shortened by eliminating certain process through the adoption of technology and machinery. Therefore, in order to enhance its current product focus strategy and preparedness for future demand, it is recommended that the company should adopt corrective strategies aiming at increasing production which include harnessing the benefits of the latest technologies through automation and machinery.